Transplant nephrectomy; pathological features of 124 consecutive cases in a single center study over 10 years - Masaki Muramatsu; Yoji Hyodo; Abigail Lee; Atsushi Aikawa; Carmelo Puliatti; Magdi Yaqoob; Michael Sheaff (Journal of Nephropathology, 2019)
Background: Transplant nephrectomy (TN) is not commonly performed but it may be essential for several indications. Objectives: This study details an in-depth evaluation of the histological changes present in TN specimens. Patients and Methods: We identified 124 consecutive TN cases between 2004 and 2014. The indication for TN was divided into four groups: acute graft loss without significant blood flow (AGL group- 47 cases); suspected ongoing rejection or graft intolerance syndrome (Rej/GIS group44 cases); infection (INF group- 24 cases); and miscellaneous reasons (MIS group- 9 cases). We examined the histological changes, including the main renal artery (MRA), intrarenal arteries, the renal vein and the ureter. Results: In AGL group, most cases showed no tubulointerstitial inflammation, interstitial fibrosis and tubular atrophy, but 74.5% had necrosis. All cases in Rej/GIS group showed severe interstitial fibrosis and tubular atrophy, since 40.9% showed severe tubulointerstitial inflammation. Glomerulitis was observed in 52.3% and transplant glomerulopathy (TG) was detected in 75.0%. Arteritis of intrarenal arteries and the MRA were detected in 70.5% and 59.1%. In INF group, 66.7% had tubulitis and 79.2% had interstitial inflammation with lymphocytes, and severe interstitial fibrosis while, tubular atrophy were detected in 66.7%. TG was detected in 62.5%. In MIS group, the histological changes were minor. Conclusions: This study provides a detailed description of the morphological characteristics associated with various indications for TN. TN will occasionally reveal unexpected and significant findings that may require specific forms of treatment to manage the patient appropriately.